2021
DOI: 10.3390/cancers13143629
|View full text |Cite
|
Sign up to set email alerts
|

Development of Multidrug Resistance in Acute Myeloid Leukemia Is Associated with Alterations of the LPHN1/GAL-9/TIM-3 Signaling Pathway

Abstract: P-glycoprotein (known as ABCB1 transporter) expression in myeloid blasts of acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS) leads to the commonly observed multidrug resistance. Overexpression of latrophilin-1 was detected in leukemic cells from AML patients. In a previous study, we showed that ABCB1 overexpression is associated with decreased latrophilin-1 expression in MOLM-13/VCR and SKM-1/VCR AML cell variants derived from MOLM-13 and SKM-1 cells by vincristine selection/adaptation. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Importantly, the sTIM‐3 secretion levels of T lymphocytes isolated from TILNs were found to increase. Unlike other sICs, such as sGalectin‐9 21 and sPD‐L1, 22 the secretion of sTIM‐3 is currently known to be completely dependent on the proteolytic cleavage of ADAM protease, but independent of alternative splicing of mRNA. 23 Thus, the expression of TIM‐3 on the cell membrane is closely related to the secretion of its soluble form.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the sTIM‐3 secretion levels of T lymphocytes isolated from TILNs were found to increase. Unlike other sICs, such as sGalectin‐9 21 and sPD‐L1, 22 the secretion of sTIM‐3 is currently known to be completely dependent on the proteolytic cleavage of ADAM protease, but independent of alternative splicing of mRNA. 23 Thus, the expression of TIM‐3 on the cell membrane is closely related to the secretion of its soluble form.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in this review, lymph nodes (where anti-tumor immune responses are elicited) and the tumor itself (where effector function is performed) are attractive anatomic sites where galectins may be inhibited. Finally, it was demonstrated that tumors generate different isoforms of galectins via alternative splicing [ 379 ]. This phenomenon can induce inhibitor-resistant galectins.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the accumulation of PSs, another important factor affecting the treatment efficacy or failure is the phenomenon of MDR. The concept of MDR is not novel, as it has been very extensively studied over the last few decades [ 10 , 150 , 151 , 152 ]. Initially, only the reduction of chemotherapy efficacy was attributed to MDR [ 10 ], but since the 1990s, there has been a growing body of evidence highlighting the fact that MDR exceeds the borders of chemotherapy and could affect other therapeutic approaches, even PDT.…”
Section: Problematic Attributes and Limitations Of Pdtmentioning
confidence: 99%